ANALISIS BILINGUALISME PADA NOVEL SUPERNOVA AKAR KARYA DEWI LESTARI - Hatma, Triesna Fuji (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2015)
This study aims to find out, how the analysis of bilingualism on Supernova novel Akar by Dewi Lestari specifically examine 1) How is the form of switch code on Novel Supernova Akar by Dewi Lestari 2) How is the form of mixed code on Novel Supernova Akar by Dewi Lestari  3) How the function context of switch code on Novel Supernova Akar by Dewi Lestari 4) How the function context of mixing code on Novel Supernova Akar by Dewi Lestari. The research data in the form of words in the novel Supernova Akar by Dewi Lestari and the source data used in this study is novel literary work entitled Supernova Akar by Dewi Lestari. The method used in this research is descriptive method. Data collection techniques used are documentation and recording techniques. The products of this research isthe use of bilingualism in Novel Supernova Akar by Dewi Lestari, formof switch codethat is used by a speaker and two speakers, mixed forms are used in order to cool the code, follow the trend, educational exhibit, showing the position and function of the context of the use of switch code and mixed code that is a) transactional function, namely the function of language to tell something to the listener ( to do something), and b) interactional function is linguistic function to maintenance social relathionship, example to negociate role relations, people with the same age solidarity, ship exchange on conversation, saving face to speaker or listener.